SISTEM HUKUM BARAT, SISTEM HUKUM ADAT, DAN SISTEM HUKUM ISLAM, MENUJU SEBAGAI SISTEM HUKUM NASIONAL SEBUAH IDE YANG HARMONI - H Mustaghfirin (Faculty of Law, Universitas Jenderal Soedirman, 2011)
West Legal System follow the philosophy of legal positivism values conflict with the noble values of the Indonesian nation, so there Gab between the law and people of Indonesia are regulated, System of Customary Law in the values of certain indigenous communities whose territory reached 350 indigenous territories, and can only be believed by public socialized habits, and can not be validated as a national law, and Islam as the Legal System is based on the attributes of God as